A multicopy sRNA of Listeria monocytogenes regulates expression of the virulence adhesin LapB - Sievers, Susanne (Oxford University Press, 2014)
The multicopy sRNA LhrC of the intracellular pathogen Listeria monocytogenes has been shown to be induced under infection-relevant conditions, but its physiological role and mechanism of action is not understood. In an attempt to pinpoint the exact terms of LhrC expression, cell envelope stress could be defined as a specific inducer of LhrC. In this process, the two-component system LisRK was shown to be indispensable for expression of all five copies of LhrC. lapB mRNA, encoding a cell wall associated protein that was recently identified as an important virulence factor, was disclosed to be directly bound by LhrC leading to an impediment of its translation. Although LhrC binds to Hfq, it does not require the RNA chaperone for stability or lapB mRNA interaction. The mechanism of LhrC-lapB mRNA binding was shown to involve three redundant CU-rich sites and a structural rearrangement in the sRNA. This study represents an extensive depiction of a so far uncharacterized multicopy sRNA and reveals interesting new aspects concerning its regulation, virulence association and mechanism of target binding.